2017
DOI: 10.4300/jgme-d-16-00235.1
|View full text |Cite
|
Sign up to set email alerts
|

Education in Neurology Resident Documentation Using Payroll Simulation

Abstract: Background Approaches for teaching neurology documentation include didactic lectures, workshops, and face-to-face meetings. Few studies have assessed their effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Studies across the nation have highlighted inadequate training for house staff with regard to billing and coding. 3 One report suggested that 82% of residents do not receive adequate training for billing and coding. 1 Careful clinical documentation is essential not only for billing but also for communication, education, data collection, quality management, and research.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies across the nation have highlighted inadequate training for house staff with regard to billing and coding. 3 One report suggested that 82% of residents do not receive adequate training for billing and coding. 1 Careful clinical documentation is essential not only for billing but also for communication, education, data collection, quality management, and research.…”
Section: Introductionmentioning
confidence: 99%
“…1 Careful clinical documentation is essential not only for billing but also for communication, education, data collection, quality management, and research. 3,4…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Educational interventions have been shown to result in improved documentation and increases in potential reimbursement. 2 We conducted a resident-led review of inpatient documentation to test the hypothesis that deficiencies in clinical documentation were responsible for incomplete International Classification of Diseases, 10th Revision (ICD-10) coding, which may have led to hospitalizations exceeding expected LOS.…”
Section: Q-tipmentioning
confidence: 99%
“…For example, Baker et al [ 3 ] developed an interpretive summary, differential diagnosis, explanation of reasoning, and alternatives assessment tool to assess comprehensive new patient admission notes. Liang et al [ 8 ] created a checklist for neurology residents” documentation. These tools are used for a specific section in medical records or a neurology department, which may not be practical for other specialties.…”
Section: Introductionmentioning
confidence: 99%